Assessing preschoolers’ approaches to learning in the Chinese context: a scale for teacher-parent co-evaluation - Feng, Lina; Wang, Jingjing (Frontiers in Psychology, 2023)
An effective assessment of preschoolers’ approaches to learning (ATL) requires multiple-reporter co-evaluation, such as teachers and parents. Based on extant research on children's ATL combined with Chinese cultural background and educational policies, this study develops an ATL scale with 20 items that are suitable for Chinese teachers and parents to co-evaluate preschoolers’ ATL. Exploratory and confirmatory factor analysis (CFA) of the data collected from teachers (n=833) and parents (n=856) demonstrates the four-factor structure of the ATL: creativity, learning strategy, competence motivation, and attention/persistence, wherein creativity is a new dimension uncovered in the Chinese context. Psychometric analysis demonstrates that the scale has good reliability and validity. Multi-group CFA further shows that the measurement model is robust and independent from reporter identity. Overall, this study contributes a novel and easy-to-use measurement instrument for educational practitioners and for scholars who are interested in cross-cultural comparison or longitudinal development of Chinese children's ATL.